2018
DOI: 10.1038/s41433-018-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

Lateral tarsal strip versus Bick’s procedure in correction of eyelid malposition

Abstract: This study compares the outcomes of the largest reported cohort of eyelid malposition surgery analyzing the two different techniques for lid margin shortening. Bick's procedure achieved statistically significant better anatomical and functional outcomes compared to LTS although the samples were unequal and not randomized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 10 publications
0
25
1
1
Order By: Relevance
“…Traditionally, lateral musculopexy is applied for mild laxity, lateral canthopexy for moderate laxity, whereas lateral canthoplasty is performed for severe laxity with an excision of 3 to 5 mm of lateral lid margin, followed by suturing the tarsal strip to the lateral orbital rim. As early as 1966, Bick's procedure, which has been described to be superior to lateral tarsal strip, was proposed to correct involutional lower eyelid malposition 20,21 . Subsequently, several modified techniques have been devised to treat ectropion of the lower eyelids.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, lateral musculopexy is applied for mild laxity, lateral canthopexy for moderate laxity, whereas lateral canthoplasty is performed for severe laxity with an excision of 3 to 5 mm of lateral lid margin, followed by suturing the tarsal strip to the lateral orbital rim. As early as 1966, Bick's procedure, which has been described to be superior to lateral tarsal strip, was proposed to correct involutional lower eyelid malposition 20,21 . Subsequently, several modified techniques have been devised to treat ectropion of the lower eyelids.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used surgical procedure for ectropion repair in our study was the Bick technique in 59.1% of the cases, followed by lateral tarsal strip -22.7%. Vahdani et al compared the functional and anatomical outcomes of lateral tarsal strip (557 cases) with Bick's procedure (87 cases) in the treatment of eyelid malposition and found that Bick's procedure achieved statistically significant better anatomical and functional outcomes compared to lateral tarsal strip although the samples were unequal (27).…”
Section: Discussionmentioning
confidence: 99%
“…Strip fixation to the inner periosteum of the lateral orbital rim at the corresponding area of Whitnall’s tubercule was performed with the use of a 5.0 double-armed braided polyester suture (Ethibond, Ethicon USA). The orbicularis muscle and skin were closed in layers with interrupted 6.0 polyglactin absorbable sutures (Vicryl, Ethicon USA) [12]. Skin sutures were removed in 1 week.…”
Section: Methodsmentioning
confidence: 99%